Critical Information Infrastructure Security 5th International Workshop, CRITIS 2010, Athens, Greece, September 2010, Revised Papers - Xenakis, Christos; Wolthusen, Stephen (Security and Cryptology ;, 2011)
This book constitutes the thoroughly refereed post-proceedings of the 5th International Workshop on Critical Information Infrastructure Security, CRITIS 2010, held in Athens, Greece in September 2010. The 12 revised full papers and two poster papers presented went through two rounds of reviewing and improvement and were selected from 30 submissions. The papers included address various techniques to realize the security of systems, communications, and data.